Peningkatan Keterampilan Manajemen RICE (Rest, Ice, Compression, Elevation) Pada Ankle sprain Dalam Cedera Olahraga Melalui Pelatihan Dengan Metode Simulasi Oleh Anggota PMR - Wibowo, Doni; Astuti, Noormailida; Kurniawan, Ahmad Rizqie; Rahmi, Eka Silvia Noor (Jurnal Keperawatan Florence Nightingale, 2024)
The lack of knowledge and skills of PMR members is one of the factors of their ineffectiveness in managing sports injuries, especially in ankle sprain injuries. Improper handling can cause more serious problems, ranging from injuries, complications, to permanent disability. RICE management training for ankle sprain in sports injuries using simulation methods can improve the skills of PMR members, because training with this simulation method, participants will find it easier to understand, remember, repeat and apply their skills. The purpose of this study was to determine the effectiveness of training with simulation methods on RICE management skills for ankle sprain in sports injuries by PMR members. The method used is quantitative research using a pre-experimental design with a one group pre-test and post-test approach with a population of 48 PMR members The sampling technique used total sampling. Respondents were given an intervention in the form of RICE management simulation training for ankle sprain in sports injuries which was given in one meeting and used a measuring instrument in the form of an observation sheet for handling ankle sprain injuries. Data analysis used the wilcoxon signed ranks test. Based on the results of the study, a p value of 0.000 was obtained (p => 0.05). Training with the simulation method has a significant effect on the level of RICE management skills in ankle sprain in sports injuries.